Pengaruh Penambahan Cabai ( Capsicum annum ) Dan Gula Terhadap Total Bakteri Asam Laktat (BAL) Dari Sauerkraut - Vauzia Vauzia; Resti Fevria; Indiastri P Monica; Moralita Chatri; Afifatul Achyar; Edwin Edwin (Postgraduate, University of Mataram, 2023)
Sauerkraut is a typical German food made from thinly sliced cabbage. Sauerkraut is a fermeted product that can give a distinctive taste. Sugar is an ingredient that can be added in, that sugar can trigger the growth of lactic acid bacteria. Indonesian people like food with a spicy sensation from chilies, chillies here contain vitamin C which functions as an antioxidant that is good for the body and is able to increase endurance. This study aims to calculate the total lactic acid bacteria contained in sauerkraut with the addition of chilies and sugar. Dilution of 1 ml sample into 9 ml physiological NaCl solution from 10 -1 to 10 -8 dilutions was carried out, then inoculated into MRS Agar using the pour plate method. Incubated in room temperature for 48 hours. The growing colonies of lactic acid bacteria were then observed based on colony morphology and counting the total growing lactic acid bacteria. The results of the research can be concluded that there was an increase in the number of lactic acid bacteria in sauerkraut with the addition of chili and 10% granulated sugar with a bacterial density average is 88.667 x 108 CFU/mL.